Therapists' Experiences with Nonverbal Communication Techniques in Psychotherapy for Children with Autism - Lai, Wang; Karevan Brojerd, Kiyana (Psychological Research in Individuals with Exceptional Needs, 2023)
This study aims to explore therapists' experiences with nonverbal communication techniques in psychotherapy for children with autism. This qualitative study employed a phenomenological approach to gain in-depth insights into therapists' experiences. Sixteen licensed therapists with at least two years of experience working with children with autism were selected through purposive sampling. Data were collected through semi-structured interviews, each lasting 60-90 minutes, and were transcribed verbatim for analysis. Thematic analysis was conducted to identify key themes and patterns in the data. NVivo software was used to facilitate the organization and analysis of qualitative data, ensuring rigor through triangulation, member checking, and maintaining an audit trail. The analysis revealed four main themes: implementation of nonverbal techniques, perceived effectiveness, challenges and barriers, and strategies for overcoming barriers. Therapists reported using a variety of nonverbal techniques such as gestures, facial expressions, eye contact, body language, and physical proximity. These techniques were perceived as highly effective in enhancing understanding, emotional connection, behavioral improvements, and self-expression in children with autism. However, challenges such as therapist-child compatibility, resource limitations, environmental factors, and inconsistent parental involvement were noted. Strategies to overcome these challenges included continuous training, collaborative approaches, adaptive techniques, creating supportive environments, and leveraging technology. Nonverbal communication techniques are essential in psychotherapy for children with autism, significantly enhancing therapeutic outcomes. Despite challenges, these techniques, when tailored to individual needs and supported by continuous training and collaboration, can greatly benefit children with autism. Future research should focus on larger and more diverse samples, quantitative measures of effectiveness, and the role of cultural sensitivity in nonverbal communication strategies.